The Effect Of Effleurage Massage Using Virgin Coconut Oil On The Risk Level Of Pressure Ulcers In Intensive Care Unit Patients - Darmareja, Rycco; Kosasih, Cecep Eli; Priambodo, Ayu Prawesti (Jurusan Keperawatan FIKES UNSOED, 2020)
Immobilising critically ill patients increases the prevalence of pressure ulcers, which can increase the length of a patient’s stay and rehabilitation, plus leading to increased pain and other complications. An independent intervention of effleurage massage using essential oil is considered to be a preventative measure for integrity anoxia, which causes pressure ulcers. The purpose of this research is to identify the effect of effleurage massage using virgin coconut oil (VCO) on the risk level of pressure ulcers in the intensive care unit. Quasi-experimental one-group pre- and post-tests were performed on 34 patients through purposive sampling using the Braden Scale. The interventions were carried out for 20 minutes on the back of the head, neck, back, glutei, sacrum, hands and feet. A dependent t-test was used in this research because it met the parametric test requirements, followed by a Repeated Measures ANOVA test. The results of the dependent t-test showed that the intervention had a significantly positive effect on pressure ulcers (p=0.0001) if effectively carried out for at least three continuous days. It was concluded that effleurage massage using VCO has a significant effect on reducing the risk level of pressure ulcers in immobilised patients.